Crisis response and management and emerging information systems : critical applications - Jennex, Murray E, 1956- (Information Science Reference, 2011)
"This book provides a comprehensive, cross disciplinary look at the advancing and understanding of organizational, technical, human, and cognitive issues associated with the use of information systems in responding and managing crises of all kinds"--Provided by publisher.